Answer:
3
Step-by-step explanation:
Simplify
3
x
2
−
x
3
x
2
-
x
.
Tap for more steps...
x
2
=
x
10
−
4
5
x
2
=
x
10
-
4
5
Move all terms containing
x
x
to the left side of the equation.
Tap for more steps...
2
x
5
=
−
4
5
2
x
5
=
-
4
5
Since the expression on each side of the equation has the same denominator, the numerators must be equal.
2
x
=
−
4
2
x
=
-
4
Divide each term by
2
2
and simplify.
Tap for more steps...
x
=
−
2
It is wrong because the equation is missing parentheses around the sum
When it says "the quantity of..." it always means parentheses. The correct equation is 2(3x+4)
That equal 1 because they are the same
Answer:
56 min
Step-by-step explanation: